2015
DOI: 10.1371/journal.pone.0117771
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing Based Characterization of Extensively Drug-Resistant Mycobacterium tuberculosis Isolates from Pakistan

Abstract: Improved molecular diagnostic methods for detection drug resistance in Mycobacterium tuberculosis (MTB) strains are required. Resistance to first- and second- line anti-tuberculous drugs has been associated with single nucleotide polymorphisms (SNPs) in particular genes. However, these SNPs can vary between MTB lineages therefore local data is required to describe different strain populations. We used whole genome sequencing (WGS) to characterize 37 extensively drug-resistant (XDR) MTB isolates from Pakistan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 66 publications
8
59
2
2
Order By: Relevance
“…47 We also observed the same when we looked into sequences of XDR strains from Pakistan that were pncA wild type and resistant to PZA. 48 …”
Section: Discussionmentioning
confidence: 99%
“…47 We also observed the same when we looked into sequences of XDR strains from Pakistan that were pncA wild type and resistant to PZA. 48 …”
Section: Discussionmentioning
confidence: 99%
“…An isolate was considered resistant to a given drug when growth of 1% or more as compared with the control was observed in drug‐containing medium. MTB H 37 Rv wild‐type strain (ATCC 27294) was used as a control for drug susceptibility testing (WHO ; Ali et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…MTB H 37 Rv wild-type strain (ATCC 27294) was used as a control for drug susceptibility testing (WHO 2009;Ali et al, 2015).…”
Section: Drug Susceptibility Testing (Dst)mentioning
confidence: 99%
“…Our study followed primer patterns from one related study in Hong Kong that could predict 96.8% specificity and 64.2% sensitivity for kanamycin from rrs on gene marker 1401 [11]. showed 78% of kanamycin resistance correlated to SNPs in rrs at nt1401 [28] and concluded that the commercial diagnostic tool determining the aminoglycoside drug resistance target at rrs nt 1401 could detect 78% of kanamycin resistance in XDR-TB isolates [28]. One related study in Thailand showed that the designed rrs primer using 3 positions and 1680 PCR product size could predict 100% specificity and 72.4% sensitivity of kanamycin resistant M/XDR-TB [29].…”
Section: Kanamycin Resistancementioning
confidence: 91%